Fungsi Musik Kalinong Dalam Kegiatan Memanen Padi Di Rantau Panjang Kelurahan Mampun Kabupaten Merangin Provinsi Jambi - Romi Afriansah; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2022)
This study aims to determine and describe how the function of Kalinong music in rice harvesting activities in Rantau Panjang, Mampun Village, Merangin Regency, Jambi Province. This type of research is a qualitative research using descriptive analysis method. The research instrument is the researcher himself and uses several tools such as writing instruments and cellphones. Data collection techniques were carried out by means of observation, interviews, literature studies and documentation. The steps in analyzing the data are collecting data, describing the data and concluding the data. The results showed that kalinong music in rice harvesting activities had three functions, namely: (1) the function of emotional expression, (2) the function of aesthetic enjoyment and (3) the function of entertainment. In the rice harvesting activity, kalinong music is played by two women, one as vocals and the other playing kalinong. Kalinong music games are still used by the people in Rantau Panjang in traditional events and traditional activities there, such as silek/silat martial arts and rice harvesting activities accompanied by kalinong music. Kalinong music is also preserved and passed down to their children and grandchildren so that Kalinong music is not lost by the times.